HAVESTADT V/S FEBRÉS. ABOUT A LETTER AND SOME SONGS - Rondón Sepúlveda, Víctor (Revista de Historia Social y de las Mentalidades, 2024)
This article examines the relationship between two treatises on mapudungún (mapuche language) published by a German Jesuit (Havestadt, 1777) and a Spanish Jesuit (Febrés, 1765), both active in Chile during the two decades prior to the expulsion of the order . From a letter allegedly written by one of them to the other and the songs contained in their works, this paper examines the plans of Compañía de Jesús in this period and the personal situations of the two missionaries. Although the Havestadt’s work was previous, the jesuit superiority it would have preferred the publication of Febrés’s text due to its closest relation with the strategy that was implemented in the years prior to the expulsion order.